Harmonization of Rules of Origin: An Agenda for Plurilateral Cooperation? - Bernard Hoekman; Stefano Inama (East Asian Economic Review (EAER), 2018)
This article discusses the deadlock in the WTO on multilateral harmonization of non-preferential rules of origin (RoO) and reviews some of the RoO included in recent preferential trade agreements. We argue that there is a trend towards adoption of similar approaches and that this suggests that cooperation to reduce the trade-impeding effects of differences in RoO across jurisdictions is more feasible than often is assumed by observers and policymakers. From a trade facilitation perspective such cooperation could be based on plurilateral initiatives under the umbrella of the WTO. These could include a focus on pursuit of greater convergence between preferential and nonpreferential RoO helping to achieve the long-standing goal of moving towards harmonization of rules of origin.
Keywords: F13; F15; F33; 330; Rules of Origin; WTO; Trade Agreements; Plurilateral Cooperation; Regulation